Mennyt maisema kaupunkipienoismallina - Siro, Susanna (Tekniikan Waiheita, 2013)
The past landscape as scale model of city The article looks at the history of scale models of cities through construction- related themes. My goal is to present the kinds of processes through which lost historical landscapes portrayed in scale models of cities have been built from idea to artifact. I have selected three cities for examples: Vyborg, Pori and Rovaniemi. Historical models of each city are on display in museums. These models display a landscape that no longer existed at the time of construction. The loss of the original landscape through destruction was one of the criteria for choosing these examples. The scale model of the city of Pori shows Pori before the great fire of 1852. It was built in Satakunta Museum’s own workshop. There are two scale models of Rovaniemi: one displaying the town in 1939, and another in 1944. These models were commissioned from a model-building company. The scale model of Vyborg portrays the city at a precise moment: on the 2 September 1939 at 10:30 am. The Vyborg scale model was also produced by a model-building company, but behind the project was a private foundation, Wiipuri-museon Säätiö. A cultural life-cycle analysis produces information on the history of reconstruction phases. It looks for reasons behind the choices made over what is included in the scale model. It is designed to examine both the process and the end result, which cannot be measured only quantitatively but also qualitatively and experientially. A cultural life-cycle analysis showed that almost the same results could be achieved from different starting points. Scale models of cities are still being built. These models and the information they generate are perceived as an important part of exhibitions in museums, and they continue to fascinate audiences.